2000
DOI: 10.1097/00007691-200002000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Concentration-Control Investigations of Mycophenolic Acid in Adults After Transplantation

Abstract: Data have emerged that provide the scientific basis for therapeutic drug monitoring of mycophenolic acid (MPA) in transplant patients receiving mycophenolate mofetil (MMF), the parent drug, in combination with other immunosuppressive agents. There is a significant relationship between the dose-interval MPA AUC and risk for acute rejection based on retrospective investigations in renal and heart transplant patients and on prospective investigations in renal transplant patients. The MPA dose-interval AUC varies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
91
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 23 publications
10
91
3
Order By: Relevance
“…Analysis of MPA concentration in the 29 Chinese patients in this study revealed that the pattern of the concentration-time profile was similar to the results of other studies (Pescovitz et al, 2003;Cho et al, 2004), although there was some variability of AUC (0−12) , C max and t max . The mean MPA AUC ((52.546±13.215) µg·h/ml) of Chinese kidney transplant patients treated with 1000 mg MMF twice daily was higher than that of Caucasian patients ((33.3±13.7) µg·h/ml), African American patients ((26.8±14.3) µg·h/ml) who took the same dose as that in our study (Shaw et al, 2000), and Korean patients ((18.45±4.25) µg·h/ml) taking MMF 750 mg twice a day. Only 3 of our 29 patients experienced acute rejection within 1 month after operation, maybe it was partly due to the high MPA AUC in the target range of 30 to 60 µg·h/ml reported to decrease the risk of acute rejection (Shaw et al, 2000).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Analysis of MPA concentration in the 29 Chinese patients in this study revealed that the pattern of the concentration-time profile was similar to the results of other studies (Pescovitz et al, 2003;Cho et al, 2004), although there was some variability of AUC (0−12) , C max and t max . The mean MPA AUC ((52.546±13.215) µg·h/ml) of Chinese kidney transplant patients treated with 1000 mg MMF twice daily was higher than that of Caucasian patients ((33.3±13.7) µg·h/ml), African American patients ((26.8±14.3) µg·h/ml) who took the same dose as that in our study (Shaw et al, 2000), and Korean patients ((18.45±4.25) µg·h/ml) taking MMF 750 mg twice a day. Only 3 of our 29 patients experienced acute rejection within 1 month after operation, maybe it was partly due to the high MPA AUC in the target range of 30 to 60 µg·h/ml reported to decrease the risk of acute rejection (Shaw et al, 2000).…”
Section: Discussioncontrasting
confidence: 51%
“…The mean MPA AUC ((52.546±13.215) µg·h/ml) of Chinese kidney transplant patients treated with 1000 mg MMF twice daily was higher than that of Caucasian patients ((33.3±13.7) µg·h/ml), African American patients ((26.8±14.3) µg·h/ml) who took the same dose as that in our study (Shaw et al, 2000), and Korean patients ((18.45±4.25) µg·h/ml) taking MMF 750 mg twice a day. Only 3 of our 29 patients experienced acute rejection within 1 month after operation, maybe it was partly due to the high MPA AUC in the target range of 30 to 60 µg·h/ml reported to decrease the risk of acute rejection (Shaw et al, 2000). But we must be careful when the patient simultaneously has CsA and MPA AUC concentrations such as above 3 acute rejection patients.…”
Section: Discussioncontrasting
confidence: 51%
“…The pharmacokinetic variability of MPA and its glucuronide using 6-h AUC was comparable to that using 12-h AUC [6][7][8]14]. Contributory factors may include concomitant medication effects as well as renal and hepatic disease (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Patients in the cyclosporin cohort were significantly older and had a significantly higher median plasma bilirubin concentration than those in the tacrolimus group (median [IQR] =13 [10][11][12][13][14][15][16][17][18] and 7 [5][6][7][8][9][10][11][12] mmol l -1 , respectively; P = 0.01). Otherwise there were no other significant differences between groups relating to race, sex, body weight, body mass index (BMI), diabetes, CAPD, transplant type, HLAM, PRA, ischaemic time, creatinine clearance, graft function or blood biochemistry.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The potential utility of monitoring plasma total mycophenolic acid (tMPA) 3 concentrations for optimizing therapy with the prodrug mycophenolate mofetil (MMF) has been demonstrated in several studies (1)(2)(3)(4)(5). Because MPA is highly protein bound, there is also a need to investigate free MPA (fMPA).…”
mentioning
confidence: 99%